Public Facility Loan System Based On Laravel To Improve Transparency In Banjaranyar Village (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Banjaranyar Village faces challenges in managing public facilities such as village halls and sports fields, which are still handled manually through notebooks or verbal communication. This manual approach is prone to recording errors and lacks transparency, making it difficult for residents to access real-time facility availability and hindering administrative efficiency. This study aims to develop a web-based facility reservation system using the Laravel framework to improve transparency and management efficiency. The research adopts a combination of case studies, surveys, and observations. The survey was conducted with 25 participants, consisting of villagers and village officials selected based on their active involvement in community activities, during October to November 2024. The system enables users to check facility availability, submit reservation requests, and manage booking data in a structured manner using a MySQL database. Testing results indicate the system performs well and improves access to information for the community. In the future, the system can be enhanced with Artificial Intelligence features and mobile applications to increase service reach and operational efficiency.